An examination of deictic terms in Tehmina’s work My Feudal Lord - Jaweria Rehmat; Asma Khan; Komal Rafique (University of Chitral Journal of Linguistics and Literature, 2024)
By applying Levinson’s theoretical framework to the complicated domain of deictic phrases, this study examined and interpreted Tehmina Durrani’s My Feudal Lord. The main linguistic component that serves as an anchor for conversation in specific spatiotemporal and social contexts was the deictic marker, which was the subject of this investigation. Knowing the different roles and effects of deictic markers in the novel’s narrative setting was the goal of the study. The pragmatic principles governing the use of deictic phrases in communication were clarified by this study’s close-textual analysis-based qualitative methodology, which drew on Levinson’s pragmatic theory. The purpose of the study was to examine how character relationships, narrative viewpoint, and sociocultural nuances in the text are affected by deictic pronouns, demonstratives, temporal adverbs, and spatial expressions. The quantitative research looked at whether deictic phrases were used most and least frequently in the work. This investigation’s fundamental idea was to apply Levinson’s framework for interpretation in order to make sense of the practical implications of deictic utterances in "My Feudal Lord." This study thoroughly examined how deictic indicators interact with verbal acts, communicative implicatures, and beliefs in an effort to uncover the text’s hidden meanings and its resonance in the socio-political context of modern-day Pakistan. Furthermore, the study underscored the significance of utilising Levinson’s theoretical framework as a lens through which to perceive the author’s narrative strategies and situated the analysis within the broader context of text interpretation and literary discourse. In the end, this study offered a thorough examination of the deictic phrases in "My Feudal Lord," improving our understanding of the pragmatic elements of language usage in literary works.